Дослідження методів моделювання інформаційного пошуку за допомогою лінгвістичних автоматів - Бєлінський, Г. А. (ХНУРЕ, 2024)
The goal of research is to develop algorithms and software based on linguistic automata for the optimization of information retrieval. Additionally, the adaptability of these methods for various search tasks is explored, along with determining the most effective strategies for utilizing linguistic automata in this context. To achieve the set goal, methods of mathematical modeling and analysis of linguistic automata are employed. Specifically, the research involves analyzing their potential in the context of optimizing information retrieval and determining optimal operating parameters.
Keywords: інформаційний пошук; лінгвістичні автомати